Economic and social background of the Tswana - Moeti, Moitsadi (Acta Academica: Critical views on society, culture and politics, 2024)
Studies of variow economies have identified three component processes involved in production: the acquisition of narural resources, labour and cools; che organisation of work tasks, and the distribution of produce. In masc cases, however, analyses of production have neglected co examine all forces with a bearing upon production. This does not mean, however, chat production forces are the determining base of an economy. Rather such an approach provides a dearer understanding of the coral organisation of production. The purpose of chis article, therefore, is co consider the following: characteristic branches of production within Tswana society in South Africa, the social relations of production and surplus extraction among masika (lineages), and the organisation of bogwera (initiation schools) as political/military